Factors influencing basic vaccination coverage in Myanmar: secondary analysis of 2015 Myanmar demographic and health survey data - Ikuma Nozaki; Masahiko Hachiya; Tomomi Kitamura (BMC, 2019)
Abstract Background Immunization is one of the most effective measures for preventing disease when vaccination coverage is sufficient. Although vaccination coverage is known to be influenced by social and cultural barriers, the determinants of childhood immunization in Myanmar remain poorly understood. This study analyzed factors that influenced complete vaccination status (one dose each for Bacillus Calmette-Guérin and measles and three doses each for diphtheria-pertussis and polio) using 2015 data from the Myanmar Demographic Health and Survey. Methods Data from 12 to 23-month-old children and their mothers were extracted from the nationally representative survey results. Bivariate and multivariate analyses with survey-weighted logistic regression were performed to examine the relationships between vaccination status and various sociodemographic and medical factors. The independent variables for the analyses included area of residence, economic status, maternal age, marital status, education, literacy, employment status, antenatal care attendance, tetanus vaccination, place of delivery, postnatal evaluations, child's sex, number of children, previous child death, decision maker(s) regarding child's health, frequency of healthcare visits, paternal education, and paternal occupation. Results A representative sample of 904 cases were extracted for the analysis. The overall complete vaccination rate was 55.4%. In the multivariate analysis with backward step-wise selection, complete vaccination was independently associated with middle or high economic status (adjusted odds ratio [AOR]: 2.64, 95% confidence interval [CI]: 1.85-3.78), older maternal age (AOR: 2.87, 95% CI: 1.62-5.10), ≥4 antenatal care visits (AOR: 1.87, 95% CI: 1.28-2.73), and maternal tetanus vaccination before delivery (AOR: 3.26, 95% CI: 1.82-5.85). Conclusion The first Demographic and Health Survey in Myanmar revealed that only approximately one-half of 12-23-year-old children had received complete vaccination, which was lower than the estimated rate from routine administrative coverage. Our results indicate that incomplete immunization status was associated with low economic status, younger maternal age, fewer antenatal care visits, and no maternal tetanus vaccination. These findings may help improve the targeting and strategic implementation of the Expanded Programme on Immunization.